Metacognition, Learning Flow and Problem Solving Ability in Nursing Simulation Learning. - Yun-Jeong Oh; Hee-Young Kang (Journal of Korean Academy of Fundamentals of Nursing, 2013)
This study was done to investigate the relationship between metacognition, learning flow, and problem solving ability in simulation learning of nursing students and to identify the factors influencing problem solving ability. Methods: The study sample was 136 nursing students. Data were collected from September to November, 2012 using a structured questionnaire on metacognition, learning flow and problem solving ability. Descriptive statistics, Pearson correlation and stepwise multiple regression analysis were used with the SPSS win 20.0 program to analyze the data. Results: There were significant positive correlations between metacognition, learning flow and problem solving ability. Learning flow was a significant factor affecting problem solving ability. These variables accounted for 33% of variance. Conclusion: These results suggest that simulation learning has a positive effect on nursing students' learning outcomes.